Here we go again: the reemergence of anti-vaccine activism on the Internet - Kenneth Rochel de Camargo Jr
Abstract: This essay discusses the resurgence of anti-vaccine activism in recent years, based on relevant literature and the author's own experiences. After presenting possible reasons for the reemergence of such movements and their consequences, the author analyses the role of Internet-mediated communication in amplifying this discourse and making it less amenable to criticism, presenting some of the main arguments deployed by the anti-vaccine agents in their discussions. The text concludes with a draft of possible responses to this increasingly worrying phenomenon.